DEVELOPMENT OF PROFESSIONAL COMPETENCE IN STUDENTS ON THE BASIS OF PROGRAMMING TECHNOLOGIES - Sa’dullayev , Avaz Akmal o‘g‘li; Oʻktamova , Sabrina Umarjon qizi (Innovative Development in Educational Activities, 2024)
The article examined the forms, tools and methods of training aimed at developing professional competence on the basis of programming technologies for students.